2008
DOI: 10.1177/1066896907313755
|View full text |Cite
|
Sign up to set email alerts
|

CD30-Positive T-Cell Lymphoproliferative Disorder of the Oral Mucosa—An Indolent Lesion: Report of 4 Cases

Abstract: Four cases of CD30-positive T-cell lymphoproliferative disorder (CD30+ LPD) of the oral mucosa are described. This article aims to draw attention to this entity and to emphasize its usual benign clinical behavior despite its resemblance to T-cell lymphoma. All the patients were adults. Three of the lesions were on the dorsal surface of the tongue and 1 affected the buccal mucosa. All biopsies showed a dense lymphoid infiltrate composed of CD30+ atypical T cells with a polymorphous infiltrate in the background,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Indolent CD30-positive T-cell lymphoproliferations have been reported previously in the oral cavity, especially the tongue, and variably designated traumatic ulcerative granuloma with stromal eosinophila, traumatic eosinophilic granuloma, eosinophilic ulcer of the oral mucosa and Riga (or Riga-Fede) disease. [11][12][13][14][15][16][17][18][19][20] These terms connote a reactive process. 17,19 Reports of seemingly similar processes have been described as lymphomatoid papulosis (in the absence of co-existing cutaneous disease) 21 or as T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indolent CD30-positive T-cell lymphoproliferations have been reported previously in the oral cavity, especially the tongue, and variably designated traumatic ulcerative granuloma with stromal eosinophila, traumatic eosinophilic granuloma, eosinophilic ulcer of the oral mucosa and Riga (or Riga-Fede) disease. [11][12][13][14][15][16][17][18][19][20] These terms connote a reactive process. 17,19 Reports of seemingly similar processes have been described as lymphomatoid papulosis (in the absence of co-existing cutaneous disease) 21 or as T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some investigators have used the term CD30-positive T-cell lymphoproliferative disorder and have suggested this spectrum of lesions represents the oral counterpart of cutaneous CD30-positive T-cell lymphoproliferative disorder. 15,16,18 However, strict criteria for these diagnostic terms have not been defined, and only more recent studies have included examination for expression of CD30. Here, we have used the term CD30-positive T-cell lymphoproliferations as it is not certain in all cases whether these are reactive or neoplastic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by a polymorphic infiltrate of T lymphocytes, B lymphocytes, histiocytes, eosinophils, and large atypical cells that often prove to be CD30+ T cells. 156,157 The large cells usually are mononuclear but may be binucleated, occasionally resembling Reed-Sternberg cells. Occasionally, molecular studies have documented a clonal T-cell population.…”
Section: Lymphoma Versus Inflammatory Processes Anmentioning
confidence: 99%
“…Eosinophils and cytotoxic large atypical CD30+ cells may be observed, with some authors considering that a subset of TUGSE could be better classified as the oral counterpart of the primary cutaneous CD30+ lymphoproliferative disorders (LPDs). [13] TUGSE with extensive vascular destruction mimicking malignant lymphoma is unusual. This angiocentric/angiodestructive growth pattern is characteristic of natural killer (NK)/T-cell lymphoma, nasal type, being rare in other LPDs.…”
Section: Introductionmentioning
confidence: 99%